Contabilidade aplicada à startup: um estudo bibliométrico dos últimos 10 anos no brasil e no mundo - Kattwinkel, Lohaine Welz (Universidade Federal do Tocantins, 2022)
The article is devoted to identify publications in the national and international literature that addressed accounting related to Startups in the last ten years. Based on the potential contribution of accounting to Startups, it is necessary to understand how existing research on this relationship exists. Therefore, through bibliometric research, a measurement of the production and dissemination of scientific knowledge in the Scopus and Spell database was carried out, building a series of standards for a bibliographic portfolio. Through this study, 198 articles were identified, and the main country to publish in accounting related to Startup was the United States, with Brazil having, no related article. The lack of studies that address the theme of accounting vs. Startup, mainly in Brazil, was elucidated, setting a precedent for new research that contributes to the management of these companies.